2019
DOI: 10.1111/mam.12172
|View full text |Cite
|
Sign up to set email alerts
|

Elevation gradients of lemur abundance emphasise the importance of Madagascar’s lowland rainforest for the conservation of endemic taxa

Abstract: 1. Elevation gradients correlate with changes in several environmental conditions and are known to influence animal abundance. Animals in regions with a naturally limited extent of lowland rainforest are expected to have evolved adaptations to intermediate elevations that provided a stable environment during their evolution. 2. Since the lowland rainforest of Madagascar has a limited extent and suffers from increasing anthropogenic pressure, it is essential to understand how well species tolerate intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 79 publications
1
21
1
Order By: Relevance
“…As all lemurs require forest habitat for their survival and many species are sensitive to habitat degradation (Schwitzer et al, 2013), I predicted that population density of all genera would correlate positively with vegetation-related variables and negatively with anthropogenic disturbance. However, due to the results of previous studies (Campera et al, 2020;Kamilar et al, 2016;Setash et al, 2017), I also predicted that population density would correlate positively with the abiotic variables temperature and precipitation, and negatively with elevation.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…As all lemurs require forest habitat for their survival and many species are sensitive to habitat degradation (Schwitzer et al, 2013), I predicted that population density of all genera would correlate positively with vegetation-related variables and negatively with anthropogenic disturbance. However, due to the results of previous studies (Campera et al, 2020;Kamilar et al, 2016;Setash et al, 2017), I also predicted that population density would correlate positively with the abiotic variables temperature and precipitation, and negatively with elevation.…”
mentioning
confidence: 87%
“…Habitat degradation and disturbance have also been demonstrated to have mostly negative effects on the population density of lemurs (Ganzhorn et al, 1997;Lehman et al, 2006a), and the population responses to these anthropogenic drivers are often reported as species-specific (Eppley et al, 2020;Herrera et al, 2011;Lehman et al, 2006b;Steffens et al, 2020). High population density variation has been observed along several environmental gradients, and there is evidence of both positive and negative correlations between lemur density and elevation (Campera et al, 2020;Goodman & Ganzhorn, 2004) and negative correlations with water availability (Axel & Maurer, 2011). There is also evidence to suggest that optimal climatic conditions (Kamilar et al, 2016), vegetation quality and productivity (Ganzhorn, 1995), and food availability (Steffens & Lehman, 2016) may also positively influence lemur population density.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Even single IRSs can be of particular importance for micro-endemic species like mouse lemurs (Radespiel et al 2008(Radespiel et al , 2012, amphibians (Gehring et al 2010;Vences et al 2010) or reptiles (Gehring et al 2010). Furthermore, the lowland rain forests of eastern Madagascar have been stated the key for lemur conservation in the long term (Campera et al 2019). At least two of these IRSs are predicted to have almost no areas of low deforestation probability (fields C7 and D8 as well as field D6 in Fig.…”
Section: Future Development In Forest Covermentioning
confidence: 99%